External jugular venous cutdown versus percutaneous technique for chemoport insertion in children: A comparative study - Veerabhadra Radhakrishna; Chittur Narendra Radhakrishnan; Ravikiran Cheelenahalli Srinivasa Rao; Gollamandala Kireeti (Wolters Kluwer Medknow Publications, 2022)
Aims: We aimed to compare the external jugular vein (EJV) cutdown technique with the percutaneous technique for difficulties in insertion, maintenance, and other complications of chemoport placement in children. Materials and Methods: A retrospective study was carried out in children who underwent chemoport insertion between January 2007 and December 2019 either by EJV cutdown or percutaneous technique in the department of pediatric surgery at a tertiary center. All children aged <18 years undergoing chemoport insertion by EJV cutdown or percutaneous technique were included in the study. Data collected included the indication, procedure time, early and late complications, and the time to removal of chemoport. Results: There was no significant difference between the EJV group and the percutaneous group in terms of the time taken for chemoport placement (40.9 ± 7.6 min vs. 37.6 ± 18.9 min; P = 0.14), failure to cannulate (one vs. six; P = 0.05), and the mean chemoport indwelling days (816.8 ± 729.2 days vs. 854.5 ± 705.1 days; P = 0.73). The chemoport placement by EJV cutdown method was found to have significantly fewer overall complications (4 vs. 14; P = 0.01) and a lesser rate of premature chemoport removal (4 vs. 12; P = 0.04) compared to the percutaneous group. Conclusions: Chemoport placement by the EJV cutdown was found to have fewer port-related complications and a lesser rate of premature chemoport removal compared to the percutaneous technique. The time taken for port placement and the mean chemoport-indwelling days were similar in both techniques.